Маркетингове дослідження ринку соняшникової олії та поведінки споживача на ньому - Арестенко, Тетяна Вікторівна; Арестенко, Татьяна Викторовна; Arestenko, Tetiana; Воронянська, Олена Владиленівна; Воронянская, Елена Владиленовна; Voronianska, Olena; Арестенко, В. В. (My University, 2020)
UK: Необхідність маркетингового дослідження ринку соняшникової олії та поведінки споживача на ньому пояснюється швидкими змінами, що відбуваються у ринковому середовищі. Правильно сформована модель поведінки споживача має бути покладена в основу подальшої стратегії розвитку підприємств, сприяти підвищенню їх конкурентоспроможності. Результати проведених польових досліджень дозволять скорегувати дії компаній з метою оптимізації їх цінової політики; підвищення ефективності взаємодії зі споживачами; підвищення впізнанності та лояльності до бренду продукції; збільшення продажів і призведуть до максимізації прибутків. EN: The need for market research on sunflower oil market and consumer behavior model on it is explained by the rapid changes occurring in the market environment. The decrease in the production of sunflower oil in Zaporizhzhia region in 2018 compared to 2017, as well as the volume of its consumption per person during this period make it urgent to conduct a study in the direction of identifying consumer motivations. Correctly formed model of con-sumer behavior should be the basis for further strategy of enterprise development, to promote their competitiveness. Research results. The study found that the most advantageous way to reach the market for businesses is to offer sunflower oil with a volume of 1.2 - 1.5 liters at a price of 23.00 to 26.00 UAH. per liter, as well as offering oil in economical packages up to 3 liters (for 17% of families with children). The most influential factor influencing the decision to buy sunflower oil is the accepted price of the product (30%), taste and confidence in the quality of the product (13% each) and the reputation of the manufacturer and the popularity of the brand (10%). ). The majority of consumers by age are people from 35 to 60 years - 67%. The largest impact on respondents is caused by advertising (37%) through television, radio and the Internet (53%), outdoor advertising (27%), print media (20%). Conclusions. The results of the study will allow you to adjust the actions of companies in order to optimize their pricing policy; increase of efficiency of interaction with consumers; increasing brand awareness and loyalty; increased sales, and as a result, will maximize profits.
Marketing research of sunflower oil market and consumer behavior on it
Keywords: маркетингові дослідження; польові дослідження; ринок соняшникової олії; анкета; опитування; інтерв’ю; респонденти; marketing research; field research; sunflower oil market; questionnaire; survey; interviews; respondents